Maksimalisasi Penyembuhan Pasien Terhadap Gangguan Halusinasi Melalui Pembelajaran Kaligrafi (Studi Intervensi Level Mikro) - Andini Kartika Sari; Fajar Utama Ritonga (Yayasan Literasi Sains Indonesia, 2022)
Mental health problems have become unresolved health problems in the midst of society, both at the global and national level. Especially in the Covid-19 Pandemic period, mental health problems will be increasingly severe to be resolved. The 2018 Basic Health Research (Riskesdas), showed that more than 19 million people aged more than 15 years experienced mental emotional disorders, and more than 12 million people aged more than 15 years of depression. One Heart To Empower Foundation (Yasam) is a social rehabilitation that focuses on dealing with drug problems and mental health problems. This foundation is located on Jalan Bunga Rampai IV, Simalingkar B, Kec. Medan Tuntungan. In the patient healing process, Yasam uses therapeutic Community method. In its application, one of the methods included in Therapeutic Community is by entering spiritual values. On this occasion the praktikan applied learning in the form of making calligraphy letters to one of the Muslim patients. This activity aims to make patients suffering from hearing hallucinations can prevent the disorder and restore focus on her.